2019
DOI: 10.1007/s40195-019-00934-y
|View full text |Cite
|
Sign up to set email alerts
|

Tension–Compression Yield Asymmetry Influenced by the Variable Deformation Modes in Gradient Structure Mg Alloys

Abstract: Surface mechanical attrition treatment (SMAT) was carried out on hot-rolled AZ31 Mg samples along two orthogonal directions; as a result, two types of gradient structures with different grain sizes and texture components in different layers were produced. The tension-compression yield asymmetry (YA) was studied using samples with different thicknesses, in order to elucidate the effect of combinations of variable deformation modes operating in different layers of the two oriented SMAT samples. The 0° oriented S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In experimental data on plastic deformations of various metals, evidence of a strong tension-compression asymmetry (TCA) behavior has been documented (i.e., see [21][22][23][24] for Mg alloys, [25,26] for body center cubic (BCC) alloys). The underlying mechanisms have been attributed to the activation of tension/compression twinning in hexagonal closepacked (HCP) alloys [27][28][29] or non-gliding forces contributing to the slip (aka non-Schmid effect) in BCC metals [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental data on plastic deformations of various metals, evidence of a strong tension-compression asymmetry (TCA) behavior has been documented (i.e., see [21][22][23][24] for Mg alloys, [25,26] for body center cubic (BCC) alloys). The underlying mechanisms have been attributed to the activation of tension/compression twinning in hexagonal closepacked (HCP) alloys [27][28][29] or non-gliding forces contributing to the slip (aka non-Schmid effect) in BCC metals [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many papers [10][11][12][13][14][15][16][17][18][19] have been focussed on this alloy and a large proportion of them report anomalies of various typesor at least effects that cannot be simply explained. Measurements on plate or sheet have consistently revealed [20][21][22][23][24][25][26] that, for loading along an in-plane direction, the yield stress in tension (~180-200 MPa) is about twice that in compression (~90-100 MPa). It has also been commonly observed that the shapes of the two (true) stress-strain curves are different, with that in tension exhibiting conventional work hardening (gradient falling off with increasing strain), but the compressive one having a sigmoidal shape, such that it rises above the tensile curve as the strain exceeds about 10%.…”
Section: Introductionmentioning
confidence: 99%